Komparasi Standar Penilaian Pendidikan di Negara-negara Maju: (Studi Kasus Finlandia, Jepang, dan Singapura) - Sihono, Sihono; Isbah, Moh Faliqul; Pangestuti , Puji (Cetta: Jurnal Ilmu Pendidikan, 2025)
Education assessment plays a vital role in determining the quality of education and students' academic performance. This study aims to analyze and compare educational assessment standards in Finland, Japan, and Singapore, exploring their relevance for developing nations. A literature review method was employed, focusing on policies and recent research. The findings reveal that Finland adopts a holistic and stress-free approach emphasizing formative assessment and individual development. In contrast, Japan prioritizes discipline and high academic standards through rigorous examinations, while Singapore utilizes competitive national exams to drive academic excellence. The study highlights that Finland fosters creativity and critical thinking, whereas Japan and Singapore emphasize competitiveness and academic achievement. In conclusion, the differing approaches of these countries reflect their educational priorities. This study offers practical recommendations for developing nations to adopt the best practices from each system to enhance their national education quality.